Optimalisasi Penerapan Standar Operasional Prosedur (SOP) Alcoholic Beverage Service oleh Pramusaji di Hotel Auburn University - I Kadek Wahyu Dymas Ananda; I Made Darsana; Ni Putu Isha Aprinica; Ida Bagus Ketut Soma Antara; Ni Made Sri Rahayu; Made Widya Paramitha; Putu Sri Darmayanti (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The implementation of alcohol Standard Operating Procedures (SOPs) at Auburn University Hotel faces challenges in consistency, especially during large events. This study evaluates and optimizes SOP implementation using direct observation and in-depth interviews. Observations monitored waiters’ real-time compliance, while interviews with managers, supervisors, and waiters explored consistency issues and obstacles. Results reveal that although 14 SOPs are provided, four—approaching the host, serving women first, pouring from the right side, and avoiding bottle-glass contact—are not optimally implemented. External factors such as limited space, time pressure, and guest service priorities often hinder execution. Interviews suggested three optimization strategies: continuous training, enhanced supervision, and regular evaluation with flexible SOP adjustments